Analysis of the selection of weather predictors to forecast dependent variables in the construction industry - Rogalska, Magdalena (Budownictwo i Architektura / Civil and Architectural Engineering, 2015)
The article shows the next steps to be taken in the project consisting in building a new home using elements of demolition of houses built of wooden beams. It was established 31 elements of the investment process, described legal requirements and details of implementation. Statistical analysis was performed with a view to determine the purchase price of the old log house. The analysis was based on data collected from an online auction. Taken into account the following data: the price of the old house, the price of 1 m2 of the house, state in which the house is built, the material from which made the roof surface.